Cultura e atividades escolares numa comunidade quilombola - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This work it is a qualitative research, a case study conducted for the following purposes: to identify and analyze the relationships established between the educational activities of a primary school and the culture of a quilombo. They are constituted as specific objectives know the process of formation of the maroon community; examine and interpret the cultural aspects pointed out by the president of Renewal Association Quilombo; describe and analyze the perception of teachers and administrators of elementary school that caters to quilombo. Most sought to understanding of education, culture, maroon communities and pedagogical activities through the case study in elementary school that caters to maroon community located in the state of Goiás. In light of Brandão (1995, 2002, 2007); Freire (1980, 1997, 2002) and Laraia (2001) analyzed the concepts of education and culture, and how they relate. Considering the African History and Afro-descendant and the slave system in colonial Brazil, the reflections were guided in Silva (2002); Hall (2011) and Moraes and Oliveira (2013), has set itself an understanding of quilombo communities and their culture, school and pedagogical activities based on the Bloc's ideas (1951); Saviani (1991); Bourdieu and Passeron (1992); Nóvoa (1995); Tardif (2002) and Treccani (2006), among other scholars who have contributed significantly to this study. The used data collection procedures consisted of observation, semi-structured interviews with the president of the association, managers and teachers, in addition to the school's Pedagogical Political Project analysis. The results show weaknesses in both the school Pedagogical Political Project as reporting managers and maroon community school teachers regarding the application of Law No. 10.639 of January 9, 2003 and the establishment of relations between the educational activities it developed and the culture of the community in which it operates. Also reveal strong identidários and ideological conflicts at school and in the wider community.
Keywords: Educação e Comunidade Quilombola; Educação Quilombola; Cultura Quilombola; Atividades Escolares em Comunidade Quilombola; Education and Community Quilombo; Quilombo education; Quilombo culture; School activities in Community Quilombo; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::ANTROPOLOGIA; CIENCIAS HUMANAS::HISTORIA